Intraocular Pressure and the Mechanisms Involved in Resistance of the Aqueous Humor Flow in the Trabecular Meshwork Outflow Pathways - Tamm, Ernst R.; Braunger, Barbara M.; Fuchshofer, Rudolf (Progress in Molecular Biology and Translational Science, 2015)
Intraocular pressure (IOP), the critical risk factor for glaucoma, is generated and maintained by the aqueous humor circulation system. Aqueous humor is secreted from the epithelial layers of the ciliary body and exits the eye through the trabecular meshwork or the uveoscleral outflow pathways. IOP builds up in response to a resistance to aqueous humor flow in the trabecular outflow pathways. The trabecular outflow resistance is localized in the inner wall region, which comprises the juxtacanalicular connective tissue (JCT) and the inner wall endothelium of Schlemm's canal (SC). Outflow resistance in this region is lowered through the relaxation of contractile myofibroblast-like cells in trabecular meshwork and the adjacent scleral spur, or the contraction of the ciliary muscle. In primary open-angle glaucoma, the most frequent form of glaucoma, outflow resistance of the inner wall region is typically higher than normal. There is evidence that the increase in resistance is related to characteristic biological changes in the resident cells of the JCT, which more and more acquire the structural and functional characteristics of contractile myofibroblasts. The changes involve an augmentation of their actin cytoskeleton and of their surrounding fibrillary extracellular matrix, which connects to JCT cells via integrins. This scenario leads to an overall stiffening of the inner wall region, and is modulated by transforming growth factor-β/connective tissue growth factor signaling. Essentially comparable changes appear to occur in SC endothelial cells. Stiffening of JCT and SC cells is very likely a critical causative factor for the increase in trabecular outflow resistance in POAG.
CRIS-Team Scopus Importer:2023-04-11
Keywords: CTGF; Glaucoma; Myofibroblast; TGF-beta; Trabecular meshwork